Reduplication in the Pendalungan Language: A Comparative Study - Siti Fitriah; Aprilia Kartika Putri; Anggi Triandana; Ulil Amri; Yoga Mestika Putra (Universitas Teknokrat Indonesia, 2023)
The purpose of this research is to describe the similarities and differences of Pendalungan`s reduplication in the Kemuningsari Kidul, Jenggawah, Jember, and East Java in terms of form, function, and meaning. The method used in this study is a comparative descriptive method whose purpose is to describe the comparison of reduplication elements of the Pendalungan language, which includes Javanese and Madurese in the Horseshoe area. The reduplication theory used relies on Simatupang's theory (1983), which divides it into five categories, namely: dwilingga, dwilingga salin suara, dwipurwa, dwiwasana, and trilingga. The object of this research is a word containing reduplication spoken by the Javanese and Madurese of the Pendalungan ethnic group. Data was collected using simak libat cakap, in which the researcher was directly involved in conversations with informants (Mahsun, 2005). The results of data analysis show that both languages consist of four forms of reduplication, namely: dwilingga, dwilingga salin suara, dwipurwa, and dwiwasana, which function as nouns, adjectives, and verbs. As well as containing plural meanings and behaviors that are carried out repeatedly. Furthermore, the patterns of Javanese and Madurese in the form of dwiwasana are different. In Javanese, the repetition of the last syllable is still placed at the end by adding a consonant /k/, such as ndelo-lok